Retracted: Conventional steroids vs. dual-release hydrocortisone on metabolic, cardiovascular, and bone outcomes in adrenal insufficiency: a 10-year study - Valentina Guarnotta; Claudia Di Stefano; Laura Tomasello; Laura Maniscalco; Giuseppe Pizzolanti; Giorgio Arnaldi; Carla Giordano (European Journal of Endocrinology, 2024)
Abstract This article has been retracted. Please see: https://doi.org/10.1093/ejendo/lvaf049